The reference of the Pronoun and Its Connection and Disconnection in Arabic - Almanan, Omer Mohammad Hamuda Atta (Journal of Humanities & Social Sciences, 2020)
The reference of the Pronoun and Its Connection and Disconnection in Arabic 1/ In the Arabic language، the pronoun sometimes refers to the first and sometimes to the second noun. 2/ The pronoun also refers to something، and it means the kind of that something 3/ The pronoun may refer to the word of the thing referred to، and its meaning، 4/ Two things may be mentioned، and the pronoun refers to one of them، most probably the second 5/ The pronoun may be attached to something، but refers to something else. 6/ Among the rules is that، if both the word and the meaning should be observed، it should be started with the word and the meaning comes next. From what has been mentioned، we understand that the pronoun is among the connective tools for the parts of the text. It acts as the word and helps avoid its repetition، connects sentences together and refers the next to the previous، and connects the end of the text with its beginning.